The Use of Tiktok in Islamic Education Learning to Instill Islamic Values in Students - Mahbubi, M; Ma'rifah, Fiki Amalia Linailil (Hikmah, 2026)
The rapid growth of short-form video platforms such as TikTok has opened new opportunities for digital-based Islamic Religious Education at MA ZAHA 04 Pakuniran. This study aims to analyze the strategies used by Islamic Religious Education teachers in utilizing TikTok as a medium for internalizing Islamic values. The study employs a qualitative approach with a case study design, collecting data through interviews, account observations, documentation, and analysis of TikTok video content. The results indicate that TikTok can serve as an engaging learning medium by presenting material in the form of short, visual, and contextual videos, such as Arabic vocabulary, moral values, Islamic motivation, the pillars of faith, and worship procedures. The use of this platform has been proven to enhance students’ motivation, engagement, and understanding of the learning material. Additionally, TikTok fosters creativity among both teachers and students in producing educational content rooted in Islamic values. However, challenges remain, particularly regarding digital literacy, video duration limitations, and the need for filtering credible content. This study concludes that TikTok has great potential as an innovative learning medium relevant to the characteristics of the digital generation, provided it is used purposefully, critically, and integrated into appropriate pedagogical strategies.